Asuhan Keperawatan Pada Pasien Dengan Penyakit Diabetes Melitus Tipe Ii Di Ruangan Muzdalifah Rumah Sakit Aisyiyah Pariaman - Olivia Aulia Putri; Mike Asmaria; Hilma Yessi; Debby Silvia Dewi (CV. ITTC INDONESIA, 2026)
According to data from the World Health Organization (WHO), the global prevalence of diabetes reached 11.11%, or approximately 589 million adults, in 2024 and is projected to increase to 853 million (12.96%) by 2050. In Indonesia, the prevalence of diabetes has risen from 5.7% in 2007 to 11.7% in 2023, with the number of cases reaching 20.4 million and expected to continue increasing. In West Sumatra, the prevalence based on physician diagnosis is 1.6%, with cases increasing from 43,464 in 2021 to more than 52,000 in 2023. The city of Pariaman has the highest prevalence in West Sumatra at 2.23%, with the number of cases continuing to rise annually. The purpose of this case study is to enable the researcher to provide nursing care for a patient with Type II Diabetes Mellitus. The research method used is a case study design, in which one patient was selected as the sample and managed through a nursing care approach. The assessment was conducted on February 9, 2026. Based on the assessment, the nursing diagnoses identified were: unstable blood glucose levels, impaired skin integrity, risk of infection, and risk of nutritional deficit. The interventions implemented included hyperglycemia management, wound care, medication administration, and nutritional management, all carried out in accordance with the established care plan. After five days of implementation, the outcomes showed a reduction in tingling in the right foot, increased comfort after dressing changes, a decrease in fever, and improved appetite. It can be concluded that appropriate nursing care can improve the patient’s health status. It is expected that the patient and family will be able to provide proper home care, anticipate potential complications, and offer support during the recovery process, maintain a healthy lifestyle—particularly in terms of diet—and utilize nearby healthcare facilities. These measures are important to ensure that the patient’s blood glucose levels remain controlled and to help prevent disease within the family.